2012
DOI: 10.1038/bmt.2012.87
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia infection in hematopoietic SCT recipients: high mortality due to pulmonary hemorrhage

Abstract: To clarify the clinical features and outcome of Stenotrophomonas maltophilia infection among hematopoietic SCT (HCT) recipients, we retrospectively reviewed the records of 1085 consecutive HCT recipients and identified 42 episodes in 31 HCT recipients with S. maltophilia infection. We compared these recipients with 30 non-HCT patients with S. maltophilia infection. The mortality rate in HCT recipients was significantly higher than that in non-HCT patients (relative risk 5.7, P ¼ 0.04), and we identified seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
4
43
0
Order By: Relevance
“…S. maltophilia causes various infectious complications in immunocompromised individuals and these include bacteremia, endocarditis, respiratory tract infections, meningitis, urinary tract infections, skin and soft tissue infections, mastoiditis, bone and joint infections, peritonitis, typhlitis and biliary sepsis, wound infections, and central venous catheter (CVC)-related infections (1–3, 5–7, 11, 15–17). Occasionally, distinguishing between colonization and infection can be problematic (1–3).…”
Section: Infections Caused By S Maltophiliamentioning
confidence: 99%
“…S. maltophilia causes various infectious complications in immunocompromised individuals and these include bacteremia, endocarditis, respiratory tract infections, meningitis, urinary tract infections, skin and soft tissue infections, mastoiditis, bone and joint infections, peritonitis, typhlitis and biliary sepsis, wound infections, and central venous catheter (CVC)-related infections (1–3, 5–7, 11, 15–17). Occasionally, distinguishing between colonization and infection can be problematic (1–3).…”
Section: Infections Caused By S Maltophiliamentioning
confidence: 99%
“…Systemic high-dose steroids are typically recommended for noninfectious cases of DAH to combat the inflammation precipitated by the underlying disease process. 9 However, research has not shown significant differences in rates of mortality between patients with DAH receiving low-, medium-, or high-dose steroids. 9 Use of platelet transfusions to treat thrombocytopenia in the setting of hemorrhage is widely accepted, but further research is necessary for the use of other treatments such as aminocaproic acid and activated factor VII.…”
Section: Treatmentmentioning
confidence: 99%
“…9 However, research has not shown significant differences in rates of mortality between patients with DAH receiving low-, medium-, or high-dose steroids. 9 Use of platelet transfusions to treat thrombocytopenia in the setting of hemorrhage is widely accepted, but further research is necessary for the use of other treatments such as aminocaproic acid and activated factor VII. Although initial study results have suggested a benefit to using aminocaproic acid in addition to steroids to treat DAH in patients who had received allogeneic HSCT, subsequent research has showed no benefit.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations